Assessment Of The Performance Loss And Repairabiity Of Earthquake Damaged Reinforced Concrete Buildings Under Repeated Earthquake - Tai, Joon Hong (Universiti Sains Malaysia, 2017)
In Sabah earthquake on 5th June 2015 with the moment magnitude of 6.0, many buildings in Sabah have experienced the structural damage due to earthquake especially for reinforced concrete buildings. The unknown of structural damage level in various buildings in Sabah and lack of clear repair standards and criteria for re-occupancy had caused the Sabah community’s seismic recovery to be taken in longer time. This study presents the results of assessment of possible variation of reinforced concrete (RC) buildings collapse vulnerability functions depending on damage state caused by potential earthquake shock. The expected building loss estimation which will be expressed in terms of performance loss (PL). S.M.K Ranau building is chosen as the case study in this research. S.M.K Ranau building was modelled in the ETABS software, and incremental dynamic analysis (IDA) was applied to develop maximum building capacity up to collapse in various damage state. Residual capacity (REC) was obtained by the simulation of seismic ground motion in Sabah on 5th June 2015, it is found that the S.M.K Ranau building experienced a drift with 0.83% and PL of 24.96%. The relatively suggested repair cost is RM413,000 based on the performance loss-cost ratio relationship graph developed.